Microbial transformation of the anti-diabetic agent corosolic acid by Cunninghamella echinulata. Issue 7 (3rd July 2017) - Feng, Xu; Lu, Yan-Hua; Liu, Zhen; Li, Dai-Ping; Zou, Ying-Xin; Fang, Yi-Qun; Chu, Zhi-Yong
Abstract: The pentacyclic triterpenoid corosolic acid was metabolized by Cunninghamella echinulata CGMCC 3.2000 to its C-24 aldehyde group metabolite and five other hydroxylated metabolites: madasiatic acid (2 ), 2α, 3β, 7β-trihydroxyurs-12-en-28-oic acid (3 ), 2α, 3β, 15α-trihydroxyurs-12-en-28-oic acid (4 ), 2α, 3β, 6β, 7β-tetrahydroxyurs-12-en-28-oic acid (5 ), 2α, 3β, 7β, 15α-tetrahydroxyurs-12-en-28-oic acid (6 ), and 2α, 3β, 7β-trihydroxy-24-al-urs-12-en-28-oic acid (7 ); compounds3, 5, and7 were new compounds. The α -glucosidase inhibitory effects of the metabolites were also evaluated.